Modification of photosynthetic electron transport and amino acid levels by overexpression of a circadian-related histidine kinase hik8 in Synechocystis sp. PCC 6803 - Kuwahara, Ayuko; Arisaka, Satomi; Takeya, Masahiro; Iijima, Hiroko; Hirai, Masami Yokota; Osanai, Takashi (Frontiers in Microbiology, 2015)
Cyanobacteria perform oxygenic photosynthesis, and the maintenance of photosynthetic electron transport chains is indispensable to their survival in various environmental conditions. Photosynthetic electron transport in cyanobacteria can be studied through genetic analysis because of the natural competence of cyanobacteria. We here show that a strain overexpressing hik8, a histidine kinase gene related to the circadian clock, exhibits an altered photosynthetic electron transport chain in the unicellular cyanobacterium Synechocystis sp. PCC 6803. Respiratory activity was down-regulated under nitrogen-replete conditions. Photosynthetic activity was slightly lower in the hik8-overexpressing strain than in the wild-type after nitrogen depletion, and the values of photosynthetic parameters were altered by hik8 overexpression under nitrogen-replete and nitrogen-depleted conditions. Transcripts of genes encoding Photosystem I and II were increased by hik8 overexpression under nitrogen-replete conditions. Nitrogen starvation triggers increase in amino acids but the magnitude of the increase in several amino acids was diminished by hik8 overexpression. These genetic data indicate that Hik8 regulates the photosynthetic electron transport, which in turn alters primary metabolism during nitrogen starvation in this cyanobacterium.